Meningkatkan keterampilan dengan pelatihan desain poster digital menggunakan canva: Improving digital poster design skills through canva training - Nurlaila, Diah; Pakiding , Fitryanti (IGKOJEI: Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT  The increasing need for visual communication skills in higher education requires students to be able to produce informative and attractive digital posters, yet many students still have limited design competence. This community service program aimed to improve the digital poster design skills of students at the Faculty of Agricultural Technology, University of Papua, through Canva-based training. The activity was conducted in three stages, namely conceptual briefing, guided tutorial, and independent practice with direct mentoring. Program evaluation used a descriptive approach through observation sheets and a poster assessment rubric covering visual composition, text readability, color suitability, layout, and design export ability. The program was implemented effectively with the active participation of 25 students, and the results showed qualitative improvement in participants' poster outputs based on the observed indicators. This training model demonstrates potential for strengthening students' applied design competence and can be continued as a follow-up digital skills development program.  Keywords: Canva Training; Digital Poster Design; Practical Training; Student Design Skills; Visual Communication   ABSTRAK  Peningkatan kebutuhan komunikasi visual di perguruan tinggi menuntut mahasiswa mampu menghasilkan poster digital yang informatif dan menarik, namun sebagian mahasiswa masih memiliki keterampilan desain yang terbatas. Kegiatan pengabdian ini bertujuan meningkatkan keterampilan desain poster digital mahasiswa Fakultas Teknologi Pertanian Universitas Papua melalui pelatihan berbasis Canva. Pelaksanaan kegiatan dilakukan dalam tiga tahap, yaitu penyampaian konsep, tutorial terstruktur, dan praktik mandiri dengan pendampingan langsung. Evaluasi program menggunakan pendekatan deskriptif melalui lembar observasi dan rubrik penilaian poster yang mencakup komposisi visual, keterbacaan teks, kesesuaian warna, tata letak, serta kemampuan ekspor desain. Kegiatan terlaksana dengan baik dengan partisipasi aktif 25 mahasiswa, dan hasil menunjukkan peningkatan kualitas luaran poster peserta secara kualitatif berdasarkan indikator yang diamati. Model pelatihan ini berpotensi memperkuat kompetensi desain aplikatif mahasiswa serta dapat dikembangkan sebagai program lanjutan peningkatan keterampilan digital. Kata kunci: Desain Grafis; Desain Poster Digital; Keterampilan Desain; Komunikasi Visual; Pelatihan Canva